KOHESI LEKSIKAL WACANA BERITA PELANTIKAN PRESIDEN DI MEDIA DARING 'TEMPO.CO' - Fadila Sukma Wijaya (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2020)
The study aims to describe and explain the results of the lexical cohesion analysis contained in Tempo.co daring media related to reporting the presidential inauguration of the October 2019 edition. The method used is in this research is a qualitative descriptive method with 3 stages: (1) searching for data, (2) analyzing data, and (3) presenting data. Research data in the form of news uploads inauguration of the president on the daring media Tempo.co in October 2019. From the results of the study there were six types of lexical cohesion, where the type of repetition or repetition of lexical cohesion is most commonly found.Â